2018
DOI: 10.3390/en11102755
|View full text |Cite
|
Sign up to set email alerts
|

A State of Charge Estimation Method Based on Adaptive Extended Kalman-Particle Filtering for Lithium-ion Batteries

Abstract: A state of charge (SOC) estimation method is proposed. An Adaptive Extended Kalman Particle filter (AEKPF) based on Particle Filter (PF) and Adaptive Kalman Filter (AKF) is used in order to decrease the error and reduce calculations. The second-order resistor-capacitor (RC) Equivalent Circuit Model (ECM) is used to identify dynamic parameters of the battery. After testing (include Dynamic Stress test (DST), New European Driving Cycle (NEDC), Federal Urban Dynamic Schedule (FUDS), Urban Dynamometer Driving Sche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…To get an accurate SOC estimation, it is vital to reduce the influences of the system noise from the complex working environment of the EVs [6]. The noise, especially the nonlinear noise, would create huge errors when estimating the SOC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To get an accurate SOC estimation, it is vital to reduce the influences of the system noise from the complex working environment of the EVs [6]. The noise, especially the nonlinear noise, would create huge errors when estimating the SOC.…”
Section: Introductionmentioning
confidence: 99%
“…In this aspect, many researchers pay their attention to improve the algorithm's accuracy or simplify the calculation process of the algorithm. From the perspective of the algorithm, the Kalman filter and particle filter (PF) are studied a lot [6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The PF requires a considerable number of initial particles and the calculation capacity is very high. In [19], the dependence of the computational load of the PF was solved using a hybrid method to estimate the SoC of a battery based on an adaptive extended Kalman particle filter (AEKPF). Five experimental tests were carried out to evaluate the performance of the algorithm and showed that the average of the absolute error was less than 1%.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 The ECM belongs to the semimechanism semiempirical model, in which the mathematical circuit expression is used to simulate the battery behavior by using the circuit elements such as voltage source, resistor, capacitor, and inductors. 23 The LIBs often exhibit some resistance-capacitance (RC) characteristics during the charge-discharge process 24 and further consider the hysteresis of open-circuit voltage (OCV) after the charge-discharge time period. 21,22 The electrical modeling method is used to simulate the working process regardless of its internal chemical reaction and therefore has good applicability.…”
mentioning
confidence: 99%
“…21,22 The electrical modeling method is used to simulate the working process regardless of its internal chemical reaction and therefore has good applicability. 23 The LIBs often exhibit some resistance-capacitance (RC) characteristics during the charge-discharge process 24 and further consider the hysteresis of open-circuit voltage (OCV) after the charge-discharge time period. 25 The problem with this equivalent modeling method is that a simple model cannot reflect the dynamic changes of the battery and may lead to incorrect recognition results.…”
mentioning
confidence: 99%